Vaccination as a Protective Factor Against Hospitalization for SARS-CoV-2 Infections: an Observational Study Using Surveillance Data - Simanjorang, Chandrayani; Tarigan, Kristin Mutiara; Sudrajat, Diva Anita Churiana; Wangsawinangun, Rana Zahra Raniyah; Zahra, Asy Syifa Anwari (UI Scholars Hub, 2025)
Death due to SARS-CoV-2 generally occurs in patients requiring hospital care (hospitalization). However, it is still unclear whether vaccination acts as a protective factor against hospitalization in SARS-CoV-2 patients in Indonesia. This study examines the association between vaccination and hospitalization among SARS-CoV-2 patients. It employs a quantitative, cross-sectional design using secondary data from SARS-CoV-2 surveillance records at the Jakarta Health Agency (January–August 2021). Findings show that patients who received the 1st vaccine dose had a 0.34 times lower risk of hospitalization compared to unvaccinated individuals (aPOR=0.34; 95% CI=0.31–0.38). Those who received the 2nd dose had an even lower risk (aPOR=0.16; 95% CI=0.14–0.18). Additionally, gender, age, and chronic kidney disease were significantly associated with hospitalization. These results indicate that vaccination reduces hospitalization risk among SARS-CoV-2 patients, even after adjusting for gender, age, and chronic kidney disease. The government should expand vaccination coverage, especially for high-risk groups. Further research is needed to assess vaccine effectiveness based on different vaccine types in preventing hospitalization in Indonesia.